From infinitely large to infinitely small: Historical reconstruction, non-fiction instance and urban stratigraphy in the work of Francesco Pecoraro (ENTHYMEMA, 2023)
The present essay aims to analyze stylistically and thematically the works of Francesco Pecoraro, paying particular attention to the novels La vita in tempo di pace and Lo stradone. Through a comparative close reading aimed at placing in mutual dialogue the two novels and the short stories collected in the volume Camere e stanze, the main objective is to investigate, on the one hand, the formal and compositional processes through which Pecoraro reworks the genre of the novel-essay and declines it according to peculiar inventive resolutions; on the other, to illuminate the expressive resources and narrative operations through which the subjectivity of his characters enters into dialectical tension with the surrounding reality and urban space.
Keywords: Francesco Pecoraro; La vita in tempo di pace; Lo stradone; Camere e stanze; Contemporary Italian Literature